HUBUNGAN KEBIJAKAN DIVIDEN, LEVERAGE, PERTUMBUHAN ASET, VOLUME PERDAGANGAN SAHAM DAN UKURAN PERUSAHAAN TERHADAP VOLATILITAS HARGA SAHAM PADA PERUSAHAAN SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Haliza, Titania Nurul; Hizazi, Achmad; Friyani, Rita (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the relationship between dividend policy, leverage, asset growth, stock trading volume, and firm size on stock price volatility in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This research employs a quantitative approach with a total sampling technique, involving 13 companies over five years of observation, resulting in 65 observations. Data analysis was conducted using panel data regression with the Fixed Effect Model after a series of classical assumption tests and model selection. The results show that dividend policy, leverage, asset growth, and firm size do not have a significant relationship with stock price volatility Meanwhile, stock trading volume has a significant relationship with stock price volatility .Furthermore, the study also provides evidence that dividend policy, leverage, asset growth, stock trading volume, and firm size significant relationship with stock price volatility. Keywords: Operational Complexity, Audit Tenure, Company Age, Profitability, Audit Delay, Good Corporate Governance